MANAJEMEN PENDIDIKAN KARAKTER BERBASIS INKLUSI UNTUK PENGUATAN SOSIAL-MORAL PESERTA DIDIK SEKOLAH DASAR - Surya Adi Saputra; Tarso Tarso; Deny Hadi Siswanto (LPMP Provinsi DKI Jakarta, 2026)
This research aims to explore in depth the management of character education for students with special needs (SEN) at SD Muhammadiyah Jogodayoh. Employing a qualitative approach with a descriptive case study design, data were collected through participatory observation, in-depth interviews with the principal and teachers, and documentation studies. The results indicate that character education management is implemented through four systematic stages. First, planning begins with multidimensional early identification and the integration of 18 character values into adaptive instructional designs. Second, organizing is carried out through classroom differentiation (regular, intensive, and transitional classes) and the implementation of co-teaching strategies to ensure equitable attention. Third, implementation focuses on the adaptation of the Merdeka Curriculum, prioritizing teacher role-modeling, religious habituation, and positive reinforcement. Fourth, routine weekly evaluations serve as quality control instruments for both student progress and teacher professional competence. The success of this model lies in the synergy between school and parents, as well as a shift in educational orientation from academic achievement to socio-moral maturity. The study concludes that structured management effectively creates a harmonious inclusive culture. It is recommended that the school strengthen collaboration with external experts and utilize assistive technology for more optimal character monitoring.